Chemical and isotopic groundwater hydrology - Mazor, Emanuel (Marcel Dekker / New York, 2004)
Contents: Introduction-chemical and isotopic aspects of hydrologic; Physical geological concepts; Chemical tools of groundwater hydrology; Isotopic tools of groundwater hydrology water identification and dating; Man and water